Quality Analysis of the Registration Information System Website using ISO/IEC 9126 Standard - Dw Ayu Agung Indra Swari; Dedy Panji Agustino; Ni Luh Komang Irma Wulandari; Yohanna Vony Sora Zalogo; Jessica Lau (Journal of Applied Informatics and Computing)
The performance of registration information systems is a crucial factor in ensuring the efficiency and effectiveness of academic administrative services. This study evaluates the quality of a registration information system based on the ISO 9126 standard, focusing on key aspects such as functionality, reliability, usability, efficiency, maintainability, and portability. The data collection methods used in this study vary based on each quality aspect. For the usability and maintainability aspects, data was collected through a questionnaire distributed to 100 respondents, consisting of students, prospective students, and academic staff. For the efficiency aspect, the GTMetrix tool was used to evaluate website performance. The reliability aspect was tested using the WAPT application. The functionality aspect was assessed using black-box testing with a total of 10 participants consisting of 2 prospective students, 5 students, and 3 administrative staff members, while portability was evaluated by accessing the website on five different mobile devices with varying screen sizes, operating systems, and types. The evaluation results indicate that the system performs well in functionality, usability, portability, reliability and maintainability but requires significant improvements in efficiency, particularly in LCP optimization. Based on these findings, optimization strategies such as image compression, CSS and JavaScript minification, and server-side caching implementation are recommended.